Hubungan Penggunaan Gadget dengan Perkembangan Balita Usia 1-3 Tahun di Desa Poncosari, Bantul, Yogyakarta - Alifia Haris Lili Prisanti; Sholaikhah Sulistyoningtyas (Jurnal Sehat Mandiri, 2024)
Bantul District Health showed that out of 57,785 children under five, early detection coverage for growth and development was only 37.76%, and delays in motor development not appropriate for age were found at 3.8%. This research aims to determine the relationship between gadget use and the development of toddlers aged 1-3 years in Poncosari Village, Bantul, Yogyakarta. This research uses an analytical survey research method with a cross sectional approach. The sample in this study was 46 toddlers aged 1-3 years and was taken using probability sampling techniques by taking simple random sampling. This research instrument uses the Gadget Use Questionnaire and KPSP Sheet. Data analysis used the non-parametric Spearman's Rho correlation test, which produced a p value (sig) of 0.000 ≤ 0.05 with a Correlation Coefficient or closeness of relationship of 0.549. The conclusion is that there is a relationship between the use of gadgets and the development of toddlers aged 1-3 years in Poncosari Village, Bantul, Yogyakarta, which is at a medium level. It is recommended that the respondent's parents be able to set limits on the use of gadgets and that there is a need for continuous parental assistance to prevent children from becoming addicted to gadgets.